ANALISIS PENGARUH ALOKASI ANGGARAN SEKTOR PERTANIAN TERHADAP PRODUKSI TANAMAN PANGAN di KABUPATEN MALANG - Mustikaningsih, Herdianti (Jurnal Ilmiah Mahasiswa FEB, 2017)
Food security program is one of the programs which made in Agricultural Development. But, as the time goes by some problems happen when Agricultural Development process applied, one of them is the global food crisis. As the effort to solve this problem, the importance of budget allocation on increasing the production is essential to the farmers. That is why this research is being held, while the research problem of this thesis is how agricultural sector’s budget allocation affects towards the production of crops. The purpose of this research is to know the effect of agricultural sector’s budget allocation towards the production of crops.In order to find the answer based on the problem which researcher had been made, the suitable method to apply is by doing the descriptive quantitative with multiple linear analysis model, both seeds and fertilizers subsidy, and also training course as the independent variable and crops production as the dependent variable. The result of the research showed the budget allocation in form of both seeds and fertilizers subsidy give such a significance effect towards the increasing of crops’ production. This happened because both seeds and fertilizers are the direct inputs in crops cultivation business and affects the production significantly. Meanwhile for budget allocation for training course also affect them significantly but inversely proportional, so when the Government decides to give additional budget to training course only will decrease the crops production.Key Words: Budget Allocation, Agricultural Sector, Agricultural Development,   The Increase of Production, Crops.